Geographic Patterns of Genome Admixture in Latin American Mestizos - Wang, Sijia; Ray, Nicolas; Rojas, Winston; Parra, Maria V.; Bedoya, Gabriel; Gallo, Carla; Poletti, Giovanni; Mazzotti, Guido; Hill, Kim; Hurtado, Ana M.; Camrena, Beatriz; Nicolini, Humberto; et al. (PLoS genetics, 2008)
The large and diverse population of Latin America is potentially a powerful resource for elucidating the genetic basis of complex traits through admixture mapping. However, no genome-wide characterization of admixture across Latin America has yet been attempted. Here, we report an analysis of admixture in thirteen Mestizo populations (i.e. in regions of mainly European and Native settlement) from seven countries in Latin America based on data for 678 autosomal and 29 X-chromosome microsatellites. We found extensive variation in Native American and European ancestry (and generally low levels of African ancestry) among populations and individuals, and evidence that admixture across Latin America has often involved predominantly European men and both Native and African women. An admixture analysis allowing for Native American population subdivision revealed a differentiation of the Native American ancestry amongst Mestizos. This observation is consistent with the genetic structure of pre-Columbian populations and with admixture having involved Natives from the area where the Mestizo examined are located. Our findings agree with available information on the demographic history of Latin America and have a number of implications for the design of association studies in population from the region.